2013
DOI: 10.1073/pnas.1314469111
|View full text |Cite|
|
Sign up to set email alerts
|

mTOR target NDRG1 confers MGMT-dependent resistance to alkylating chemotherapy

Abstract: A hypoxic microenvironment induces resistance to alkylating agents by activating targets in the mammalian target of rapamycin (mTOR) pathway. The molecular mechanisms involved in this mTOR-mediated hypoxia-induced chemoresistance, however, are unclear. Here we identify the mTOR target N-myc downstream regulated gene 1 (NDRG1) as a key determinant of resistance toward alkylating chemotherapy, driven by hypoxia but also by therapeutic measures such as irradiation, corticosteroids, and chronic exposure to alkylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
153
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 159 publications
(155 citation statements)
references
References 24 publications
0
153
0
2
Order By: Relevance
“…1A). Higher NDRG1 expression has been associated with enhanced DNA repair through increased MGMT protein stability/activity (Weiler et al ., 2014). We therefore measured NDRG1 and MGMT protein expression in liver, skeletal muscle (upper leg), and kidney from our three slow‐aging mice models fed ad lib.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Higher NDRG1 expression has been associated with enhanced DNA repair through increased MGMT protein stability/activity (Weiler et al ., 2014). We therefore measured NDRG1 and MGMT protein expression in liver, skeletal muscle (upper leg), and kidney from our three slow‐aging mice models fed ad lib.…”
Section: Resultsmentioning
confidence: 99%
“…It have been suggested that MGMT may play a role in regulating mouse lifespan (Meira et al ., 2014), but it is not known whether long‐lived mice, such as Snell, GHRKO, and PAPPA‐KO, have altered expression of MGMT. Higher expression of NDRG1, a protein of unknown function, can promote MGMT protein stability and activity in human glioma cells by mechanisms that include protein interactions and preferential translation (Smalley et al ., 2014; Weiler et al ., 2014). Therefore, understanding the signaling pathways regulating MGMT and NDRG1 may provide insights into resistance to DNA damage, chemotherapy, and the aging process.…”
Section: Introductionmentioning
confidence: 99%
“…These cells in turn may be sensitized by treatment with bone morphogenetic protein 2 (BMP2), which can down-regulate HIF-1α-mediated MGMT induction [45]. Induction of resistance may also be conferred by the hypoxia-and steroid-inducible N-myc downstream-regulated gene (NDRG1), which binds to and thus probably sustains action of MGMT [46]. Recent studies addressed a further level of MGMT regulation through direct binding of specific miRNAs to the 3'-UTR of MGMT transcripts, which may lead to decreased mRNA stability and/or reduced protein translation [47].…”
Section: Regulation Of Expression and Function Of Mgmtmentioning
confidence: 99%
“…Cell proliferation (Cell Index) was checked using the xCELLigence Real-Time Cell Analyzer (RTCA) instrument according to the instructions of the supplier (Roche Applied Science and ACEA Biosciences, San Diego, CA, USA). This system has been extensively used in other studies (8,9). The xCELLigence system can quantify the electrical impedance across electrodes at the bottom of each well of the tissue culture plates.…”
Section: Drug Cytotoxicity Analysis and Real Time Analysis Of Cell Prmentioning
confidence: 99%